Adrenal Failure: An Evidence-Based Diagnostic Approach - Shaikh, Salomi; Nagendra, Lakshmi; Shaikh, Shehla; Pappachan, Joseph M. (Diagnostics (Basel), 2023)
The diagnosis of adrenal insufficiency (AI) requires a high index of suspicion, detailed clinical assessment including detailed drug history, and appropriate laboratory evaluation. The clinical characteristics of adrenal insufficiency vary according to the cause, and the presentation may be myriad, e.g. insidious onset to a catastrophic adrenal crisis presenting with circulatory shock and coma. Secondary adrenal insufficiency (SAI) often presents with only glucocorticoid deficiency because aldosterone production, which is controlled by the renin angiotensin system, is usually intact, and rarely presents with an adrenal crisis. Measurements of the basal serum cortisol at 8 am (<140 nmol/L or 5 mcg/dL) coupled with adrenocorticotrophin (ACTH) remain the initial tests of choice. The cosyntropin stimulation (short synacthen) test is used for the confirmation of the diagnosis. Newer highly specific cortisol assays have reduced the cut-off points for cortisol in the diagnosis of AI. The salivary cortisol test is increasingly being used in conditions associated with abnormal cortisol binding globulin (CBG) levels such as pregnancy. Children and infants require lower doses of cosyntropin for testing. 21-hydoxylase antibodies are routinely evaluated to rule out autoimmunity, the absence of which would require secondary causes of adrenal insufficiency to be ruled out. Testing the hypothalamic–pituitary–adrenal (HPA) axis, imaging, and ruling out systemic causes are necessary for the diagnosis of AI. Cancer treatment with immune checkpoint inhibitors (ICI) is an emerging cause of both primary AI and SAI and requires close follow up. Several antibodies are being implicated, but more clarity is required. We update the diagnostic evaluation of AI in this evidence-based review.